Effect of Supplier Selection on Supplier Performance for Project Success with the Structural Equation Modeling Approach: Pengaruh Pemilihan Supplier Terhadap Kinerja Supplier Untuk Keberhasilan Projek dengan Pendekatan Structural Equation Modelling - Pramono, Puji; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2019)
In effort to minimize project failures (time delay) arising from due to supplier selection errors that have an impact on low performance and low potential for successful projects. This study aims to find out how strong the influence of supplier selection is right and correlates with good performance so thatthe project's success can be achieved. By using the SEM (Structural Equation Modeling) method in a PLS (Partial Least Square) application by examining the relationship between factors on the criteria of quality supplier selection that is expected to have an impact on the performance of a good supplier, and later can be related to the potential success of the project. Test results on Bootstrapping obtained the value of T-Value and P-Value in the 1st Hypothesis, namely, T-Statistics 0.829 and P-Value 0.407, the supplier performance variable (X2) did not affect the project success variable (Y1). The second hypothesis is, with a T-Statistical value of 2.094 and a P-Value of 0.037, the Supplier Selection (X1) has a significant effect on the project success variable (Y1). The third hypothesis is, with a T-Statistic value of 8.306 and a value of P-Value 0,000, Supplier Selection (X1) has a significant effect on the Supplier Performance variable (X2).